Human capital and gender development in economic growth: A case study of Sumatera Barat, 2010–2022 - Rahmasari, Fita Dinda; Ramadhani, Ratih (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2024)
This study analyzes the impact of the Human Development Index (HDI), Gender Development Index (GDI), and unemployment rate on economic growth in Sumatra Barat from 2010 to 2022. Economic growth, measured by Gross Regional Domestic Product (GRDP) per capita, reflects regional welfare. It is essential to understand the factors influencing it, particularly the quality of human resources and employment opportunities. According to data from BPS, economic growth in Sumatera Barat remains low compared to other provinces on the island of Sumatra. This study employs a dynamic panel data model using the Generalized Method of Moments (GMM) approach to address potential endogeneity issues arising from the reciprocal relationship between independent variables and economic growth. The findings indicate that HDI has a positive and significant effect on economic growth, suggesting that improvements in education, healthcare, and living standards contribute to economic expansion in Sumatera Barat. Similarly, GDI has a significant positive effect, highlighting the crucial role of gender equality in human development and driving economic growth. In contrast, the unemployment rate has a negative and significant impact, demonstrating that high unemployment hinders regional economic progress.